MANAJEMEN PERSEDIAAN OBAT PADA RUMAH SAKIT - Ria Satyarini (Bina Ekonomi, 2009)
Inventory is everything that organization can use or keep. Inventory is the most expensive assets of many companies, that's why organization have to manage their inventory. Hospital is one of the organization that have to manage their inventory very well, because drugs is very expensive and very crucial for the patient and hospital. The objective of inventory management at hospital is to balance between inventory management and customer  service.